2010
DOI: 10.1111/j.1743-6109.2010.01837.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Erectile Dysfunction in Taiwan: Use of the Erection Hardness Score and Quality of Erection Questionnaire

Abstract: Introduction There are currently no studies in the Asia-Pacific region using the erection hardness score (EHS) and Quality of Erection Questionnaire (QEQ) to assess erectile dysfunction (ED). Aims To provide up-to-date data on the prevalence of ED in Taiwanese men and to validate the EHS and QEQ in this population. Methods A representative sample of 1,060 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 24 publications
0
57
1
1
Order By: Relevance
“…Our aim was instead to evaluate the degree of patient satisfaction when either unassisted or medically assisted EF recovery (defined using different IIEF‐EF domain score cut‐offs) was achieved. Finally, despite previous studies have reported a significant association between EF and patient satisfaction [27,30], it is possible that other outcomes not considered in this study (i.e., improvement in couple relationship and in ED‐related distress, bother, and anxiety) might represent more accurate end points to be associated with EF recovery after surgery.…”
Section: Discussionmentioning
confidence: 75%
“…Our aim was instead to evaluate the degree of patient satisfaction when either unassisted or medically assisted EF recovery (defined using different IIEF‐EF domain score cut‐offs) was achieved. Finally, despite previous studies have reported a significant association between EF and patient satisfaction [27,30], it is possible that other outcomes not considered in this study (i.e., improvement in couple relationship and in ED‐related distress, bother, and anxiety) might represent more accurate end points to be associated with EF recovery after surgery.…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of ED in our study (62.4%) is similar to several population-based studies 10–12 . Given the geographical and cultural variation, the statistical data of the prevalence of ED range from 16.1% to 80.8% 11, 1315 with considerable differences. Hence, ED is a worldwide detriment to male health, and the influential factors need to be well clarified for diagnose and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ED is an important worldwide issue, affecting 152 million men in 1995 and 322 million men in 2025 and negatively impacts life quality, self-esteem, and intimacy [2], [3]. One telephone survey of ED prevalence in Taiwan reported that nearly thirty percent of men over 30 years had ED [4]. This medical problem has been associated with endothelial dysfunction and low-grade vascular inflammation and often clusters with hypertension, diabetes mellitus, hyperlipidemia, obesity, and metabolic syndrome [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%